2013
DOI: 10.1111/jvim.12251
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thoracic Auscultation, Clinical Score, and Ultrasonography as Indicators of Bovine Respiratory Disease in Preweaned Dairy Calves

Abstract: BackgroundThe diagnostic tools for bovine respiratory disease diagnosis include clinical inspection, thoracic auscultation, and ultrasonography.HypothesisThoracic auscultation and clinical examination have limitations in the detection of lung consolidation in dairy calves.AnimalsProspective cohort of 106 preweaned calves from 13 different dairy herds (10 with a history of active bovine respiratory disease (BRD) in calves and 3 without suspected BRD problems).MethodsEach preweaned calf was clinically inspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
163
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 27 publications
8
163
2
5
Order By: Relevance
“…Clinical evaluation was performed using the CRSC as described, with a cut‐off of 5 or more defining a positive test . The AUSC was performed on the entire thoracic projection as described, using a conventional stethoscope . An abnormal AUSC was defined by presence of increased bronchial sounds or presence of abnormal sounds (ie, crackles and wheezes or total absence of lung sounds) or both.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical evaluation was performed using the CRSC as described, with a cut‐off of 5 or more defining a positive test . The AUSC was performed on the entire thoracic projection as described, using a conventional stethoscope . An abnormal AUSC was defined by presence of increased bronchial sounds or presence of abnormal sounds (ie, crackles and wheezes or total absence of lung sounds) or both.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, several clinical examination scores have been developed to improve its accuracy, with moderate success . For veterinarians, diagnosis of BP is typically based on presence of visual signs of respiratory disease and abnormal lung sounds at thoracic auscultation (AUSC), including increased bronchial sounds, crackles, wheezes, or absence of respiratory sounds . Thoracic auscultation is rapid and easy to perform under field conditions, but abnormal lung sounds can also result from causes other than respiratory disease, which calls into question accuracy of AUSC for BP diagnosis.…”
mentioning
confidence: 99%
“…A potential limitation of our study was that only 1 side of the thorax was examined in 30% of the cattle. In previous studies in both beef and dairy cattle, slight to moderate agreement was found between the right and left sides of the thorax for ultrasonographic diagnosis of consolidation. Perhaps, we did not capture the maximal depth or maximal area of lung consolidation in all cattle.…”
Section: Discussionmentioning
confidence: 83%
“…Buczinski et al (2014) showed that adding the clinical score assessment to thoracic auscultation and thoracic ultrasonography, increased sensitivity of BRD diagnosis in pre-weaned Dairy Calves, although it decreases specificity when compared with lung consolidation findings. The recommendation of the WI CHSC is to treat calves because of high BRD presumption if the score is ≥5, and to monitor calves with scores of 4.…”
Section: Resultsmentioning
confidence: 97%